Advances and challenges in genetic technologies to produce single-sex litters - Douglas, Charlotte (PLoS Genet, 2020)
There is currently a requirement for single-sex litters for many applications, including agriculture, pest control, and reducing animal culling in line with the 3Rs principles: Reduction, Replacement, and Refinement. The advent of CRISPR/Cas9 genome editing presents a new opportunity with which to potentially generate all-female or all-male litters. We review some of the historical nongenetic strategies employed to generate single-sex litters and investigate how genetic and genome editing techniques are currently being used to produce all-male or all-female progeny. Lastly, we speculate on future technologies for generating single-sex litters and the possible associated challenges.